Flood Risk Assessment using Analytical Hierarchy Process and Geographic Information Systems - Jeefoo, Phaisarn; Preedapirom, Watcharaporn; Chinkeeree, Chatchadawan (Defence Technology Academic Journal, 2021)
Floods are natural disasters that damage lives and properties. This academic paper aims to review the literature on geospatial technology, introduction to geographical quantitative methods for analysis of factors affecting flooding in Pua Subdistrict, Pua District, Nan province. The research method was based on factor analysis using an analytical hierarchy process (AHP) model which the flood disaster experts rate the factor weight and land and building information survey. The results of the study revealed that there were 6 factors affecting flood risk consist of rainfall, slope, elevation, land use, and soil series respectively. Local government officials or disaster prevention and mitigation agencies can apply the principles of this study to more precisely and accurate assess areas at risk of future flooding.